(untitled) (Global Journal of Management and Business Research, 2019)
Organizational culture, ethics, and values are important aspects. Each organization has a different culture, even if in the same industry. It is important for organizations to hire employees who have the same beliefs, ethics, and values with the organization. Wells Fargo Bank is one of the biggest and well-known banks in the US. It was established in 1852 and continued to grow over the years. Recently, the bank started to have some issues and bank started to get a bad reputation. These issues were high employee turn-over rates, sales pressure, unethical practices, and lack of communication between managers and employees. Wells Fargo#x2019;s training based on product knowledge, sales strategies, and regulations. Wells Fargo is missing the importance of diversity training. The company needs to train its employees to create a better work environment. Training of managers, effective two-way communication, providing job security for employees, setting up attainable sales goals can help Wells Fargo Bank to keep trained employees, get a better reputation and increase the number of customers and sales.